The effect of soil conditions on the cost of construction projects - Booyens, Derick (University of Pretoria, 2014)
In certain areas soil of poor quality can be found and in order to build on it, the soil must be altered. This can be done by means of stabilization or modification of the soil or one can replace the poor quality soil with good quality soil. This soil improvements or replacement of the soil will have an impact on the construction cost therefore one should consider various options like the cost of stabilization versus the replacement of the poor quality soil. If soil improvements or replacement of the soil are ineffective, impractical or too expensive; foundations can be used either alone or in combination with the soil improvements. The most basic types of foundations are spread footings and strip foundations and are mostly and effectively used in good, stable soils. Other foundation types like pad foundations, raft foundations and piling foundations are more complex foundation types and are mostly used where the soils are of poor quality or unstable.